Struktura in mikrostruktura jeklenih peskov, narejenih v Abrasivu Muta - Rudolf, Rebeka (Kovine zlitine tehnologije, 1999)
In Slovenia the firm Abraziv Muta is the only producer of cast steel shot. They have the world competitor, one is Whelebrator Allevard France. This paper deals with the microstructure comparison of cast steel shot produced in Abraziv Muta with shot made in that competitor. After American standard SAE J827 the samples of shot were prepared and the defects of shot were determined. The samples were macrostructural and microstructural estimated. Hardness test, wear resistance and screening analyses of steel cas shot were also done. The results show that the cast steel shots of Abrazive Muta and French company were comparable, while the Rumanian shots were worse.
Keywords: abrazivni materiali; pesek; mikrostruktura; napake